Culturally Relevant Model for Digital Language and Literacy Instruction - Eutsler, Lauren; Pérez, Araceli (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
Overwhelming instructional technology options leave teachers searching for efficient approaches to foster differentiated instruction. This study examined an iterative, design-based research approach of one teacher’s 10-week digital literacy and language-guided small-group instructional intervention with second-grade unidentified language learners. Students explored 15 language and literacy apps, engaged in personalized reading experiences, and created authentic artifacts reflective of their culture. Findings led to the Culturally Relevant Model for Digital Language and Literacy Instruction, a roadmap for teachers and teacher educators to plan tailored instruction to better meet the needs of identified and unidentified students’ language and literacy skills.